Outcomes of decompressive craniectomy for malignant middle cerebral artery stroke in an academic hospital in Brazil - Rodrigues de Oliveira, Luiz Fernando; Camilo, Millene Rodrigues; Franciscatto, Luisa; Podolsky-Gondim, Guilherme Gozzoli; Alves, Frederico Fernandes Alessio; Filho, Rui Kleber do Vale Martins; Dias, Francisco Antunes; Tanaka, Koji; Colli, Benedicto Oscar; Pontes-Neto, Octávio Marques (Arquivos de Neuro-Psiquiatria, 2023)
Background Ischemic stroke is an important cause of death in the world. The malignant middle cerebral artery infarction (MMCAI) has mortality as high as 80% when clinically treated. In this setting, decompressive craniectomy is a life-saving measure, in spite of high morbidity among survivors.Objective To evaluate the outcomes of patients with MMCAI treated with decompressive craniectomy in a Brazilian academic tertiary stroke center.Methods A prospective stroke database was retrospectively evaluated, and all patients treated with decompressive craniectomy for MMCAI between January 2014 and December 2017 were included. The demographics and clinical characteristics were evaluated. The functional outcome, measured by the modified Rankin Scale (mRS), was assessed at hospital discharge, after 3-months and 1-year of follow-up.Results We included 53 patients on the final analysis. The mean age was 54.6 ± 11.6 years and 64.2% were males. The median time from symptoms to admission was 4.8 (3–9.7) hours and the mean time from symptoms to surgery was 36 ± 17 hours. The left hemisphere was the affected in 39.6%. The median NIHSS at admission was 20 (16–24). The in-hospital mortality was 30.2%. After a median of 337 [157–393] days, 47.1% of patients had achieved favorable outcome (mRS ≤ 4) and 39.6% had died.Conclusion Decompressive craniectomy is a life-saving measure in the setting of MMCAI, and its effects remains important in the scenario of a middle-income country in real-world situations.
Keywords: Stroke; Decompressive Craniectomy; Infarction, Middle Cerebral Artery